Manipulation of Product Weight in Same-Day Grab Delivery by Seller Marketplace Tokopedia Medan City Perspective of DSN MUI Fatwa No. 112/DSN-MUI/IX/2017 - Yuda, M.; Marlina Tarigan, Tetty (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This research is motivated by the phenomenon of product weight manipulation by Tokopedia sellers for the Grab Same Day courier service. The determination of the rates for the Grab Same Day courier service using the system of weight per kilogram of goods causes sellers to manipulate the weight of goods to be sent to consumers through the Grab Same Day delivery service. Therefore, in this study, the authors formulated the problem, namely: 1) What is the practice of product weight manipulation by the Tokopedia marketplace seller for grab same-day courier services? 2) What is the perspective of the Fatwa of the MUI National Sharia Council No. 112/DSN-MUI/IX/2017 against product weight manipulation? This study aims to find out and analyze 1) The practice of manipulating product weight by the seller marketplace Tokopedia for grab same-day courier services, 2) The Fatwa Perspective of the MUI National Sharia Council No. 112/DSN-MUI/IX/2017 on product weight manipulation. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out by conducting library research as well as field research as well as interviewing Grab Same Day drivers. The results of the study show that e-Commerce transactions on the Tokopedia marketplace have not fully complied with the provisions contained in the DSN-MUI Fatwa Number 112/DSN-MUI/IX/2017, that is, they have not fully complied with the provisions of ujrah (goods) in terms of quantity because there are some goods that are not in accordance with the Sharia, where the weight of the goods does not match the net weight, net content, or net, does not match the size, dosage, and scale according to the actual size.